Hubungan Gambaran CT Scan Toraks Dan Manifestasi Klinis Pada Pasien Coronavirus Disease 2019 (COVID-19) - Paat, Lydia; Mamesah, Yovana P. M.; Rondo, Alfa G. E. Y. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: World Health Organization has assigned COVID-19 as a pandemic. It has been reported that pulmonary abnormalities are found in asymptomatic cases. In addition, several studies have reported normal CT images in symptomatic patients. Currently, research that discusses the relationship of the image of chest CT scan and clinical manifestations of COVID-19 hasnâ€™t been done much. The aim of the study was to know the relationship between the image of chest CT scan and clinical manifestations in COVID-19 patients. This research is a literature review by searching data using three databases namely PubMed, Science Direct and RSNA. The keywords used are COVID-19 AND chest CT AND clinical manifestations. After being selected based on inclusion and exclusion criteria, there were 11 literatures consisting of 10 retrospective studies and 1 retrospective case series report. Bilateral ground glass opacity, distributed peripherally, and distributed in peripheral, appearing in the lower lobe of the lungs are the common abnormalities images in COVID-19 patients. In severe-critical cases of COVID-19, consolidation, distributed centrally and peripherally, and occurred throughout the lung lobes were significantly more common than in moderate cases of COVID-19. In addition, the total severity score and the total lesion volume increased according to the clinical classification of COVID-19. There is a significant relationship between the image of chest CT scan and clinical manifestations based on the number of lobes, distribution, presence of consolidation, total severity score, and lesion volume.Keywords: coronavirus disease 2019, chest, computed tomographyÂ Â Abstrak: World Health Organization (WHO) telah menetapkan COVID-19 sebagai suatu pandemi. Telah dilaporkan bahwa ditemukan suatu kelainan paru pada kasus asimptomatik. Selain itu, beberapa penelitian juga melaporkan adanya gambaran CT normal pada pasien bergejala. Saat ini, penelitian yang membahas hubungan gambaran CT scan toraks dan manifestasi klinis COVID-19 belum banyak dilakukan. Penelitian ini bertujuan untuk mengetahui hubungan gambaran CT toraks dan manifestasi klinis pada pasien COVID-19. Penelitian ini berbentuk literature review dengan pencarian data menggunakan tiga database yaitu PubMed, Science Direct, dan RSNA. Kata kunci yang digunakan adalah COVID-19 AND chest CT AND clinical manifestations. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, didapatkan 11 literatur terdiri dari 10 retrospective study dan 1 retrospective case series report. Ground glass opacity bilateral, multilobus, terdistribusi di perifer, dan terjadi di lobus bawah paru merupakan gambaran abnormal yang umum didapat pada pasien COVID-19. Pada kasus berat-kritis COVID-19, gambaran konsolidasi, lesi yang terdistribusi sentral dan perifer, dan terjadi di seluruh lobus paru secara signifikan lebih sering terjadi daripada kasus moderat COVID-19. Selain itu, total severity score dan total volume lesi meningkat seiring dengan meningkatnya keparahan suatu kasus COVID-19. Terdapat hubungan yang signifikan antara gambaran CT toraks dengan manifestasi klinis berdasarkan jumlah lobus, distribusi, adanya konsolidasi, total severity score, dan volume lesi.Kata Kunci: coronavirus disease 2019, toraks, computed tomography